The Chennai glaucoma study: Prevalence and risk factors for glaucoma in cataract operated eyes in urban Chennai - George, Ronnie (Medknow Publications, 2010)
We report the prevalence and risk factors for glaucoma among aphakes and pseudophakes in 3850 subjects who participated in a population-based study in urban south India. The subjects underwent an ophthalmic examination including applanation tonometry, gonioscopy, optic disc evaluation and frequency doubling perimetry. Glaucoma was diagnosed using the International Society of Geographical and Epidemiological Ophthalmology (ISGEO) criteria. Thirty eight, 15 aphakes and 23 pseudophakes (0.99% of 3850 subjects) of the 406 persons who had undergone cataract surgery were diagnosed with glaucoma. Aphakes/pseudophakes were at higher risk of glaucoma as compared to the phakic population (Odds Ratio: 2.71, 95% CI: 1. 94, 3.38, p=0.001). On multivariate analysis, older age and higher intra ocular pressure were risk factors for glaucoma. Blindness attributable to glaucoma was detected in 20% of aphakic and 4.3% of pseudophakic eyes. Glaucoma was a significant cause of morbidity in those who had undergone cataract surgery in this urban population.